Risk Management of Occupational Safety and Health (K3) Against B3 Medical Waste Management at the Regional Hospital of Kotabumi North Lampung Regency, Indonesia - Trigunarso, Sri Indra (Universitas Aisyah Pringsewu, 2021)
The implementation of Occupational Health and Safety is an endeavor to provide a safe, healthy, and pollution-free work environment in order to decrease or eliminate work accidents and occupational diseases, which can boost efficiency and production (sustainable, 2014). The level of occupational safety and health risk that waste management officers face from tasks such as selection, freight, and storage. This is a qualitative sort of research that uses the process of in-depth understanding of a topic by looking at it for generalization research (Drs. Sumanto, M.A., 1995). B3 medical waste management officers at regional hospitals face a high level of workplace safety and health risks, according to the researcher. The risk assessment is made up of the following items based on the results of the hazard identification: selection of hospital medical waste with the greatest risk of being exposed to sharp items, with a value/score of (16) indicating a high-risk Muscle and bone injuries are the highest risk in hospital medical waste freight, with a score of (12) with High Risk, and bad smell is the highest risk in unwell medical waste storage, with a score of (15) with High Risk. Risk Analysis: Selection of Hospital Medical Waste from each waste-producing room (Exposed to sharp items) and Hazardous Waste Storage are two risk statements and the statement with the highest cause in Risk Analysis (Respiratory Disorders). Evaluation of the effect of the Highest Opportunity Risk (Likelihood) x Impact (Consequence) on waste storage (bad smell) and hospital medical waste selection from each waste generating room (Exposed to Sharp Objects). Suggestions for research; adequately supervise so that things don't happen that could be really hazardous (very high). Hospitals can issue a warning or sanctions to officers who manage solid medical waste improperly.Pelaksanaan Keselamatan dan Kesehatan Kerja (K3) merupakan upaya untuk menciptakan lingkungan kerja yang aman, sehat, bebas dari pencemaran lingkungan, sehingga dapat mengurangi dan atau terbebas dari kecelakaan kerja dan penyakit akibat kerja yang pada akhirnya dapat meningkatkan efisiensi serta meningkatkan produktivitas kerja (lestari, 2014). Besarnya tingkat risiko keselamatan dan kesehatan kerja terhadap penyakit akibat kerja yang dapat terjadi pada petugas pengelolaan limbah dari kegiatan pemilihan, pengangkutan, dan penyimpanan. Jenis penelitian ini adalah bersifat kualitatif dengan metode pemahaman secara mendalam terhadap suatu masalah dari melihat permasalahan untuk penelitian generalisasi (Drs. Sumanto. M.A.,1995) peneliti ingin mengetahui besarnya tingkat risiko keselamatan dan kesehatan kerja terhadap petugas pengelolaan limbah medis B3 di Rumah Sakit Daerah. Dari hasil Identifikasi bahaya penilaian risiko terdiri dari: Pemilihan limbah medis Rumah Sakit terdapat risiko tertinggi adalah terkena benda tajam dengan nilai/skor (16) dengan risiko High, Pengangkutan Limbah medis Rumah Sakit terdapat risiko tertinggi adalah Cidera oror dan tulang dengan nilai/skor (12) dengan Risiko High, dan Penyimpanan Limbah Medis Sakit terdapat risiko tertinggi adalah Bau Tidak Sedap dengan nilai/skor (15) dengan Risiko High. Analisis Risiko terdapat 2 pernyataan risiko dan pernyataan yang paling tinggi penyebabnya yaitu, Pemilihan Limbah Medis Rumah Sakit dari setiap ruangan penghasil limbah (Terkena benda tajam), dan Penyimpanan Limbah B3 (Gangguan Pernafasan). Evaluasi dampak Risiko Peluang (Likehood) x Dampak (Consequance) yang tertinggi pada Penyimpanan Limbah (Bau Tidak Sedap) dan Pemilihan Limbah Medis Rumah Sakit Dari Setiap Ruangan Penghasil Limbah (Terkena Benda Tajam). Saran penelitian; melakukan pengawasan dengan baik agar tidak terjadi hal-hal yang dapat menimbulkan risiko yang sangat tinggi (Very High). Pihak Rumh Sakit dapat memberikan teguran atau peringatan serta sanksi agar petugas bersikap baik dalam penanganan limbah medis padat.